Synthesis and mechanical properties of flax fabric reinforced geopolymer composites - Assaedi, H.; Alomayri, T.; Shaikh, Faiz; Low, I. (TECHNO-PRESS, 2014)
Geopolymer composites reinforced with different layers of woven flax fabric are fabricated using lay- up technique. Mechanical properties, such as flexural strength, flexural modulus and fracture toughness of geopolymer composites reinforced with 2.4, 3 and 4.1 wt% flax fibres are studied. The fracture surfaces of the composites are also examined using scanning electron microscopy. The results show that all the mechanical properties of the composites are improved by increasing the flax fibre contents. It is also found that the mechanical properties of flax fabric reinforced geopolymer composites are superior to pure geopolymer matrix. Micro-structural analysis of fracture surface of the composites indicated evidence of various toughening mechanisms by flax fabrics in the composites.